Early versus delayed computed tomography-guided celiac plexus neurolysis for palliative pain management in patients with advanced pancreatic cancer: a retrospective cohort study - Lu, Fan; Wang, Xiaojia; Tian, Jie; Li, Xuehan (Frontiers in Neurology, 2023)
Abdominal and back pain is the most frequent symptom in patients with pancreatic cancer, with pain management being extremely challenging. This study aimed to evaluate pain control, opioid consumption, pain-interfered quality of life, and survival after early and delayed computed tomography (CT)-guided celiac plexus neurolysis (CPN).Methods: A retrospective analysis of pancreatic cancer patients receiving CPN for pain (n = 56) between June 2018 and June 2021 was done. The patients were grouped as early group (n = 22) and delayed group (n = 34) on the basis of the presence of persistent refractory pain according to Expert Consensus on Refractory Cancer Pain.Results: Both groups were comparable in demographic characteristics and baseline pain conditions measured using the Numeric Rating Scale (5.77 ± 1.23 vs. 6.27 ± 1.21; p = 0.141). The pain scores were significantly reduced in both groups; early CPN resulted in significantly lower scores from 3 to 5 months. The opioid consumption gradually decreased to a minimum at 2 weeks but increased at 1 month (35.56 ± 30.14 mg and 50.48 ± 47.90 mg, respectively); significantly larger consumption from 2 to 4 months was seen in the delayed group. The total pain interference was lower than baseline in all patients, with significant improvement after early CPN in sleep, appetite, enjoyment of life, and mood.The average survival time of the two groups was comparable.Early application of CT-guided CPN for patients with advanced pancreatic cancer may help reduce pain exacerbation and opioids consumption, without influencing the survival.